2019
DOI: 10.1155/2019/5186831
|View full text |Cite
|
Sign up to set email alerts
|

A Semianalytical Approach for Production of Oil from Bottom Water Drive Tight Oil Reservoirs with Complex Hydraulic Fractures

Abstract: In order to improve the recovery rate, fractured horizontal wells are widely used in tight reservoirs. In general, a complex fracture system is generated in tight reservoirs to improve oil production. Based on the fractal theory, a semianalytical model is presented to simulate a complex fracture system by using the volumetric source method and superposition principle, and the solutions are determined iteratively. The reliability of this model is validated through numerical simulation (Eclipse 2011); it shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Routinely, more than three clusters are perforated in each fracturing stage, and the horizontal lateral section is fractured stage by stage from toe to heel of the horizontal wellbore. e stages and perforation clusters are placed evenly in a horizontal wellbore, but, the rate of gas produced from each stage is different significantly, and recent studies have demonstrated that one in four perforation clusters is not producing actually, and this is almost a common phenomenon in shale gas plays [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Routinely, more than three clusters are perforated in each fracturing stage, and the horizontal lateral section is fractured stage by stage from toe to heel of the horizontal wellbore. e stages and perforation clusters are placed evenly in a horizontal wellbore, but, the rate of gas produced from each stage is different significantly, and recent studies have demonstrated that one in four perforation clusters is not producing actually, and this is almost a common phenomenon in shale gas plays [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%